Incidence of actionable findings on contrast enhanced magnetic resonance angiography ordered for pulmonary embolism evaluation. Issue 8 (August 2016) - Schiebler, Mark L.; Ahuja, Jitesh; Repplinger, Michael D.; François, Christopher J.; Vigen, Karl K.; Grist, Thomas M.; Hamedani, Azita G.; Reeder, Scott B.; Nagle, Scott K.
Abstract: Purpose: To determine the incidence of actionable findings on contrast-enhanced magnetic resonance angiography (MRA) scans performed for the primary diagnosis of pulmonary embolism (PE). Materials and methods: This was a HIPAA-compliant and IRB-approved single center, retrospective study of consecutive series of patients evaluated with contrast-enhanced MRA for PE. The final radiology report of each MRA was reviewed. All technically adequate negative exams were included in the analysis. The findings were divided into three types: those requiring further action (actionable—Type 1) those not requiring follow-up (non-actionable—Type 2) and normal exams. We compared our results with the literature regarding the use of computed tomographic angiography (CTA) in this scenario using Fisher's exact test. Results: 580 MRA scans for PE were performed. There were 561/580 (97%) technically adequate exams. Of these, 514/580 (89%) were negative and 47/580 (8%) were positive for PE. In the PE negative group of 514 exams, Type 1 findings were identified in 85/514 (17%), 188/514 (36%) cases were Type 2 and 241/514 (47.0%) were Type 3. There was no significant difference between the incidence of Type 1 and the combination of Type 2 and Type 3 findings on MRA and the reported incidence of actionable findings derived from CTA negative exams for PE (p < 0.5). Conclusion: MRA as a first-line test for PE can identify actionable findings in those patients without PE, with an incidence similar to that reported in the literature for CTA.